The Islamic Approach to Health Prevention - Abdelkader Djafer (مجلة الاجتهاد للدراسات القانونية والاقتصادية)
Health is a great blessing from Allah Almighty, through which we preserve our capacities and fulfill our responsibilities. This raises an important question: What is Islam’s methodology in health prevention? The study aims to clarify the Islamic approach in this regard, employing a descriptive methodology supported by analysis and foundational investigation. It is structured into five key sections: the first defines health prevention; the second explores Islam’s establishment upon a preventive approach; the third presents various supporting evidences; the fourth discusses preventive causes and means; and the fifth addresses the Islamic ruling on adopting preventive measures. Among the key findings is that Islam places significantly greater emphasis on prevention than on treatment, and it mandates the adoption of measures to prevent health-related harm. The study recommends further exploration of the legal rulings concerning safety and preventive measures in both Islamic jurisprudence and civil law.